A experiência esquecida: violações de direitos humanos dos povos indígenas e o direito à reparação integral - da ditadura militar à justiça de transição - Silva, Nayara Trajano Seixas da (2021)
The literature gap explored in this master thesis was the lack of studies related to the severe human rights violation of indigenous people of northern Brazil during the military dictatorship, as well as the low number of researches related to the measures taken by the State during the transitional justice’s process for those people. Knowing the growing relevance of indigenous related research in the country, legal studies related to indigenous people is vital, since the identities and differences of those people were neglected for several years. The lack of visibility regarding this research’s theme, as presented throughout the thesis, is due to that most of the researches analyzed were only occasional researches done during Brazil’s re-democratization until the establishment of the Comissão Nacional da Verdade, when the topic gained relevance. From that standpoint, the analysis performed in this research was structured in three blocks with interrelated matters. The first block is related to Brazil’s military dictatorship, historical background, origins, strengthening of the authoritarian regime, and its impact in the northern region. The second block presents how the government treated the indigenous people during the regime, as well as the political approach taken by bodies in charge of indigenous’ related matters in Brazil. Moreover, in this step, it is presented the human rights violation of indigenous people, a topic related to Relatório Figueiredo and its consequences, along with Waimiri-Atroari’s case. The third block addresses transactional justices concept’s origin and the elements of transactional justice, followed by transactional justice for indigenous people, the legal protection of their rights, the role of the Comissão Nacional da Verdade and the Comitê Estadual de Direito à Verdade, à Memória e à Justiça do Amazonas, concluding with full damage remediation entitled as a result of the human right violations and human rights of indigenous people. In conclusion, this research’s goal is to stop the State’s erasure of the human rights violation of indigenous people in northern Brazil during the military dictatorship, especially in Amazonas state, in addition to the study of the legal protection of indigenous people to know the paths to ensure their rights